1973
DOI: 10.1002/1097-0142(197303)31:3<729::aid-cncr2820310337>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary thymic seminoma—a neoplasm ultrastructurally similar to testicular seminoma and distinct from epithelial thymoma

Abstract: Epithelial thymoma and thymic seminoma, which are important to distinguish for therapeutic reasons, are often confused histologically. The purpose of this study is to compare the ultrastructural appearances of a primary thymic seminoma, a classical testicular seminoma, and an epithelial thymoma. The thymic seminoma shows many ultrastructural similarities to the classical testicular seminoma in that the tumor cells have bizarre nucleoli, relatively scanty organelles, abundant glycogen, and are rounded or polyhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…After teratoma, seminoma is the second most common germ cell tumor of the mediastinum in its pure form 19, 20. However, the true incidence of seminomas has been difficult to assess due to the relatively small series of cases reported until now 21‐46. In our experience, primary mediastinal seminomas have accounted for approximately 37% of all mediastinal germ cell tumors and taken second place only to teratomas.…”
Section: Discussionmentioning
confidence: 76%
“…After teratoma, seminoma is the second most common germ cell tumor of the mediastinum in its pure form 19, 20. However, the true incidence of seminomas has been difficult to assess due to the relatively small series of cases reported until now 21‐46. In our experience, primary mediastinal seminomas have accounted for approximately 37% of all mediastinal germ cell tumors and taken second place only to teratomas.…”
Section: Discussionmentioning
confidence: 76%
“…Nonetheless, such tumors have also been described in other locations, such as the pineal gland, retroperitoneum, mediastinum, and sacral area 2‐4. Germ cell tumors arising primarily in the mediastinum are uncommon and have mostly been the subject of case reports; very few comprehensive studies on this topic have been reported in the literature 2, 4‐103. It has been estimated in some studies that extragonadal germ cell tumors account for approximately 1‐15% of mediastinal tumors in adults and approximately 25% in children 21, 59, 60, 104…”
mentioning
confidence: 99%
“…[89] Focal weak staining with p53 IHC was observed in 31% of mediastinal seminomas and 77% of testicular seminomas. Eight percent of mediastinal seminomas showed K-ras mutation (codon 13 GGC > GAC; glycine > aspartate), which is in contrast to 15% of testicular seminomas showing codon 12 mutations.…”
Section: Discussionmentioning
confidence: 99%